The Elements of C++ Style - Misfeldt, Trevor; Bumgardner, Gregory; Gray, Andrew; Xiaoping, Luo (Cambridge University Press, 2004)
The Elements of C++ Style, first published in 2004, is for all C++ practitioners, especially for those working in teams where consistency is critical. Just as Strunk and White's The Elements of Style provides rules of usage for writing in the English language, this text furnishes a set of rules for writing in C++. The authors offer a collection of standards and guidelines for creating solid C++ code that will be easy to understand, enhance and maintain. The book provides conventions for: • formatting • naming • documentation • programming • and packaging for the latest ANSI standard of C++, and also includes discussion of advanced topics such as templates.